Live-attenuated YF17D-vectored COVID-19 vaccine protects from lethal yellow fever virus infection in mouse and hamster models - Ji Ma; Michael Bright Yakass; Sander Jansen; Bert Malengier-Devlies; Dominique Van Looveren; Lorena Sanchez-Felipe; Thomas Vercruysse; Birgit Weynand; Mahadesh Prasad Arkalagud Javarappa; Osbourne Quaye; Patrick Matthys; Tania Roskams; et al. (EBioMedicine, 2022)
Summary: Background: The live-attenuated yellow fever vaccine YF17D holds great promise as alternative viral vector vaccine platform, showcased by our previously presented potent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine candidate YF-S0. Besides protection from SARS-CoV-2, YF-S0 also induced strong yellow fever virus (YFV)-specific immunity, suggestive for full dual activity. A vaccine concomitantly protecting from SARS-CoV-2 and YFV would be of great benefit for those living in YFV-endemic areas with limited access to current SARS-CoV-2 vaccines. However, for broader applicability, pre-existing vector immunity should not impact the potency of such YF17D-vectored vaccines. Methods: The immunogenicity and efficacy of YF-S0 against YFV and SARS-CoV-2 in the presence of strong pre-existing YFV immunity were evaluated in mouse and hamster challenge models. Findings: Here, we show that a single dose of YF-S0 is sufficient to induce strong humoral and cellular immunity against YFV as well as SARS-CoV-2 in mice and hamsters; resulting in full protection from vigorous YFV challenge in either model; in mice against lethal intracranial YF17D challenge, and in hamsters against viscerotropic infection and liver disease following challenge with highly pathogenic hamster-adapted YFV-Asibi strain. Importantly, strong pre-existing immunity against the YF17D vector did not interfere with subsequent YF-S0 vaccination in mice or hamsters; nor with protection conferred against SARS-CoV-2 strain B1.1.7 (Alpha variant) infection in hamsters. Interpretation: Our findings warrant the development of YF-S0 as dual SARS-CoV-2 and YFV vaccine. Contrary to other viral vaccine platforms, use of YF17D does not suffer from pre-existing vector immunity. Funding: Stated in the acknowledgments.